Pelatihan Penerapan IoT (Internet of Things) Melalui Perancangan Smart City untuk Siswa SMA Negeri 1 Tomohon dan SMA Kristen 1 Tomohon - Berton Maruli Siahaan; Maria Daurina Bobanto; Afrioni Roma Rio (Jurnal Lentera: Penelitian dan Pengabdian Masyarakat, 2025)
The Internet of Things (IoT) plays an essential role in the era of the fourth industrial revolution and the Smart City concept, now increasingly implemented across various sectors, including education. This technology enables remote access and monitoring of multiple devices, supporting efficiency and responsiveness in information management. In the educational context, introducing IoT technology at the high school level aims to equip students with foundational knowledge and skills, better preparing them for future technological advancements. This training was conducted at SMA Negeri 1 Tomohon and SMA Kristen 1 Tomohon, focusing on temperature monitoring as part of a Smart City simulation. The temperature monitoring system introduced allows real-time data access through internet and mobile devices, offering students a concrete experience of IoT’s potential in daily life. During the training, students had the opportunity to observe and interact with pre-designed devices, gaining insights into installation processes, connectivity, data collection, and data processing. Evaluation results indicate that the program successfully enhanced students' understanding and interest in IoT technology, as well as strengthened their motivation to engage with relevant digital technology developments. This training is expected to be an initial step towards enabling students to use IoT as an innovative solution in the future.